Macrolides properties, synthesis and applications - Arsic, Biljana, 1980- (De Gruyter, 2018)
"Macrolides, a class of natural macrocyclic products, are among the most clinically important antibiotics. The authors introduce the different classes of macrolides and their derivatives, principles of their biological activity, as well as synthesis methods of macrolide antibiotics"--Provided by publisher.